La Sostenibilidad Financiera en el Sector Cooperativo de la Economía Popular y Solidaria en Ecuador - Apolo Paladines, Elanny Samantha (2023)
Studies related to financial sustainability have received little attention in Ecuador, despite the importance of promoting the long-term strengthening of organizations. Therefore, the research proposes to evaluate the financial sustainability of the cooperative sector of the Popular and Solidarity Economy in the period 2015-2020. In this context, the research analyzed longitudinal information, with a quantitative approach. An analysis of the structure of the cooperative sector is presented, which was complemented by a correlational study of financial sustainability that took as reference the dimensions proposed by the theory. Additionally, using the Syalom model, an integrated scorecard is proposed to strengthen the financial sustainability of the cooperative sector of the Popular and Solidarity Economy in Ecuador. Finally, the results indicate that the financial situation of the organizations decreased due to the COVID-19 pandemic and that leverage and profitability are relevant variables in the financial sustainability of organizations.